2021
DOI: 10.1093/mnras/stab160
|View full text |Cite
|
Sign up to set email alerts
|

Massive black holes in high-redshift Lyman Break Galaxies

Abstract: Several evidences indicate that Lyman Break Galaxies (LBG) in the Epoch of Reionization (redshift z > 6) might host massive black holes (MBH). We address this question by using a merger-tree model combined with tight constraints from the 7 Ms Chandra survey, and the known high-z super-MBH population. We find that a typical LBG with MUV = −22 residing in a Mh ≈ 1012M⊙ halo at z = 6 host a MBH with mass M• ≈ 2 × 108M⊙. Depending on the fraction, fseed, of early halos planted with a direct collapse black h… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 141 publications
0
4
0
Order By: Relevance
“…IFrom another point of view, the discrepancy between the UV and X-ray QLFs at the faint end would be explained by the fact that only bright quasars outshining their host galaxies can be identified as point-like sources in the rest-UV quasar selection (M18; Adams et al 2020;Ni et al 2020;Bowler et al 2021;Orofino et al 2021;Kim et al 2022). However, at the faint end of M 1450  −24 mag, extended sources such as the brightest galaxies at z ∼ 6 dominate over quasars in number at the same UV magnitude (Harikane et al 2022b).…”
Section: Resultsmentioning
confidence: 99%
“…IFrom another point of view, the discrepancy between the UV and X-ray QLFs at the faint end would be explained by the fact that only bright quasars outshining their host galaxies can be identified as point-like sources in the rest-UV quasar selection (M18; Adams et al 2020;Ni et al 2020;Bowler et al 2021;Orofino et al 2021;Kim et al 2022). However, at the faint end of M 1450  −24 mag, extended sources such as the brightest galaxies at z ∼ 6 dominate over quasars in number at the same UV magnitude (Harikane et al 2022b).…”
Section: Resultsmentioning
confidence: 99%
“…The power-law shape of the bright end of the high-z galaxy UV luminosity function (Bowler et al 2020;Donnan et al 2022) suggests that BH accretion could substantially contribute to the UV luminosity of these systems. Indeed, at z ∼ 6, the number density of galaxies in −22 M UV −20 (Bowler et al 2020) is only a factor of a few higher than the active galactic nucleus (AGN) densities at the same magnitudes (Giallongo et al 2019;Orofino et al 2021), suggesting a high Open squares are REBELS sources from Bouwens et al (2022), open hexagons are REBELS sources with τ 1500 estimated by Ferrara et al (2022), and open triangles are Lyα emitters from Endsley et al (2021). The solid line is the best-fit power law ; E 1500 0.63 t l µalso shown is the adopted functional form for E eff l (red dashed), the range of likely values (dark green), and the outflow region (light and dark green).…”
Section: Discussionmentioning
confidence: 99%
“…Although other mechanisms related to AGN feedback may produce such an observable, by, for instance, preventing gas infall from large scales (e.g., Trussler et al 2020) or causing fluctuations in the gravitational potential, which may lead to a radial migration of the material (e.g., van der Vlugt & Costa 2019), Barai et al (2018) found that the mechanical removal of gas from the inner region of the host galaxies is the main process that affects their gas content in their simulations. We underline that also some 5 < z < 7 star-forming (1 − 70 M yr −1 ) galaxies have been found to show both an extended [C II] halo (e.g., Fujimoto et al 2020) and broad wings in the [C II] emission-line profile (e.g., Gallerani et al 2018;Ginolfi et al 2020), suggestive of outflows possibly powered by a yet undetected accreting MBH (e.g., Orofino et al 2021).…”
Section: Discussionmentioning
confidence: 71%